"Being or becoming physically active": unpacking conceptions about objectives and methods in partnership-based alternative sports activities. Issue 4 (1st October 2020) - Högman, Johan; Augustsson, Christian; Hedström, Pernilla
Abstract: Few intervention programmes focussing on increasing physical activity among children have been successful long term. It has also become increasingly common among scholars as well as politicians to advocate for organisations within a field to 'join up' to tackle social challenges. Research indicates that collaborative processes may entail challenges in implementing programmes informed by high quality knowledge. The aim of this study was, therefore, to examine partner organisations' conceptions about objectives of an alternative sports programme, how such objectives are meant to be achieved, and how such conceptions may affect children's development of a physically active lifestyle. Qualitative content analysis revealed three underlying lines of thought regarding alternative activities for children, as follows: they should increase the member base through modifications; they should awaken the inherent desire to move through targeting motor skills; and they should transform sports clubs by providing an exercise arena. The article discusses how activities fail to consider children's predisposing factors and what implications this has for the work of promoting children's physical activity. Finally, we suggest that partnerships would benefit from applying a multi-leveled ecological model when designing programmes.